Analysis of Character Education Values in 4th Grade Student Thematic Books in the 2013 Curriculum - Ujang Jamaludin; Awiria Awiria; Ajat Sudrajat; Asrori Yudha Prawira (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aimed to analyze the values of character education in the thematic books of 4th-grade Curriculum 2013 students. Textbooks or teaching materials are among the most important learning tools in stimulating, advancing, educating, and improving the nation's welfare and having a meaningful role in student achievement. The importance of teaching materials as a medium for internalizing educational values, teaching materials should be packaged based on character education. The research was conducted at SDN Tanah Tinggi 7 Tangerang City in the 4th-grade skills. The method used is qualitative research. The data source used was the thematic book of the 2013 curriculum for the 4th-grade students. The data were obtained using content review techniques, observation, and interviews. Data analysis is done by using content analysis systematically on the thematic books being studied. The results showed that half of the 4th grade have loaded character values contracted in the 2013 curriculum. Values curriculum most common character is the character value friendly, communicative and likes to read. Meanwhile, the least character value found was the character value of the national spirit